Konsep Pendidikan Islam menurut Persis dalam Konteks Pembelajaran Fiqh Tingkat Mu’allimien (sebuah penelitian etnografhi tentang pendidikan dalam persis 2013) - Mumu Zainal Mutaqin (LPPM STAI La Tansa Mashiro, 2015)
The unity of Islam or what we often know ’’ exactly '' is one of the religious organizations in Indonesia, which was established on 12 September 1923 in Bandung. In carrying out its vision and mission Exactly establishing various types and levels of educational institutions that are quite different in the concept of education and in this case the study intends to specifically discuss the level of mu'allimien educational institutions. This research emerged from the premise that the existence of Persis as a religious mass organization in Indonesia has provided a different paradigm, fiqh which is the subject of discussion as an icon of difference, intrigued the writer to conduct research, but because the author was in the scope of education, the author took fiqh context as teaching material at one of the levels of Pesis education namely mu'allimien. Mu'allimien is the level of education institutions that are equivalent to high school where after graduating from mu'allimien students can continue their tertiary education full of community haterogens, so here the author tries to explore this with the formulation of the problem 1. (What is the concept of Islamic education exactly? , 2). How do you think about the curriculum level of the multi-level curriculum? What is the curriculum and learning process at the mu'allmien level of fiqh? To find answers to the problem formulation, the author uses the 'naturalistic qualitative' method by collecting data through documentary or library studies, observations, interviews and questionnaires. So based on the data collection that writing uses, the author can conclude that the concept of Islamic education is exactly to realize the Muslim personality that is tafaquh fid dien, from the description of the vision and mission, then precisely providing the concept of formal, non-formal and informal education and from the concept divided into four , namely pesantren outside the pesantren, school and outside the school. Particularly for the formal education program, Persis then provides a range of pre-school education, elementary schools, the first high school, high school and university. The Mu’allimien is one of the most formal types of school education. This Mu'allimien is provided to provide the mu'allim or the teacher in particular and to provide a servant of Allah who is ready to go down in the community, so in order to achieve this goal in the final assignment of this mu'allimien education program students are required to practice teaching, PLKJ (Khidmat Jami'yyah Training Program) and writing scientific papers, must also go through a comprehensive oral examination as a concrete form of the absorption of learning that has been conveyed. Fiqh as one of the teaching materials that exist in mu'allimien aims to transfer the science of knowledge which in this case is Exactly. In piqh learning, the method used in fiqh learning is not different from other learning learning, as long as the method is good and right then that is what is used. Fiqh as one of the icons that became a conversation among the community because of the difference. In studying fiqh at the level of mu'allimien this is only introduced, and there is no special discussion exclusively that addresses how fiqh, NU (Nahdatul Ulama) or Muhammadiyah. Basically the writer wants to convey that the difference in the interpretation of law is a necessity, the most important thing is the science of charity, because charity without knowledge is taqlid Al Isro: 36 Persatuan Islam atau yang sering kita kenal ‘’persis’’merupakan salah satu ormas keagamaan yang ada di Indonesia,yang berdiri tanggal 12 september tahun 1923 di Bandung. Dalam melaksanakan visi dan misinya Persis mendirikan berbagai jenis dan tingkat lembaga pendidikan yang cukup berbeda dalam konsep pendidikanya dan dalam hal ini penelitian bermaksud untuk khusus membahas pada lembaga pendidikan tingkat mu’allimien. Penelitian ini muncul dari dasar pemikiran bahwa adanya Persis sebagai ormas keagamaan di Indonesia telah memberikan suatu paradigma yang berbeda, fiqh yang menjadi bahan perbincangan sebagai icon adnaya perbedaan tersebut menggelitik penulis untuk melakukan penelitian, namun di karna kan penulis ada dalam lingkup pendidikan, maka penulis mengambil konteks fiqh sebagai bahan ajar di salah satu tingkat pendidikan Pesis yakni mu’allimien. Mu’allimien adalah tingkat lembaga pendidikan yang setara dengan SMA dimana setelah lulus dari mu’allimien siswa bisa melanjutkan pendidiakn keperguruan tinggi yang penuh dengan haterogensi masyarakat,maka disini penulis mencoba untuk menggali hal tersebut dengan rumusan masalah 1.(Bagaimana konsep pendidikan islam persis?, 2).Bagaiman kurikulum tingkat mu’allimien ?,Bagaimana kurikulum dan pe,belajaram fiqh tingkat mu’allmien? Untuk menemukan jawaban dari rumusan masalah tersebut, maksa penulis menggunakan metode’’kualitatif naturalistic’’dengan cara mengumpulkan data melalui studi documenter atau pustaka,observasi,interview dan kuesioner. Maka berdasarkan pengumpulan data yang menulis gunakan, penulis bisa menyimpulkan bahwa konsep pendidikan islam Persis adalah untuk mewujudkan kepribadian muslim yang tafaquh fid dien,dari gambaran visi dan misi tersebut,maka persis menyediakan konsep pendidikan formal,nonformal dan informal dan dari konsep tersebut terbagi kepada empat,yaitu pesantren luar pesantren, sekolah dan luar sekolah. Khusus untuk jejang pendidikan formal Persis maka Persis menyediakan jejang pendidikan pra sekolah,Sekolah Dasar,Sekolah Menegah Pertama,Sekolah Menegah Atas dan Perguruan Tinggi. Mu’allimien adalah salah satu jejang pendidikan Persis formal yang berjenis sekolah. Mu’allimien ini di sediakan untuk menyediakan para mu’allim atau guru khususnya dan untuk menyediakan seorang hamba Allah yang sudah siap turun di masyarakat,maka dalam rangka menuju tujuan tersebut dalam tugas akhir program pendidikan mu’allimien ini para siswa wajib melakukan peraktek ngajar, PLKJ (Program Latihan Khidmat Jami’yyah)dan menulis karya tulis ilmiah,juga harus dengan melalui ujian lisan komprehensif sebagai bentuk kongkrit dari penyerapan pembelajaran yang telah di sampaikan. Fiqh sebagai salah satu bahan ajar yang ada di mu’allimien bertujuan untuk mentransfer ilmu kepiqihan yang dalam hal ini adalah Persis. Dalam pembelajaran piqh, metode yang digunakan dalam pembelajaran fiqh tidak berbeda dengan pembelajaran pembelajaran yang lain,selama metode itu bagus dan tepat maka itulah yang di gunakan. Fiqh sebagai salah satu icon yang menjadi perbincangan di kalangan masyarakat karena perbedaanya. Dalam mempelajari fiqh di tingkat mu’allimien ini hanya sekedar di kenalkan, dan tidak ada pembahasan khusus secara eksklusif yang membahas bagaimana fiqh, NU (Nahdatul Ulama) atau Muhammadiyah.Pada dasarnya penulis ingin menyampaikan bahwa adanya perbedaan dalam interprestasi hukum merupakan sebuah keniscayaan,yang terpenting adalah ilmu dalam beramal, karena amal tanpa ilmu adalah taqlid Al Isro :36